New synonymies and transfers in Castianeira Keyserling, 1879 (Araneae, Corinnidae, Castianeirinae) from India - Sankaran, Pradeep M.; Caleb, John T.d.; Sebastian, Pothalil A. (Zootaxa, 2019)
Indian species in the castianeirine genus Castianeira Keyserling, 1879 (Corinnidae) are partly revised based on type materials deposited in the National Zoological Collection, Zoological Survey of India, Kolkata. Two new synonyms are recognized: Castianeira himalayensis Gravely, 1931 syn. nov. is synonymised with Corinnomma severum (Thorell, 1877), and Castianeira bengalensis Biswas, 1984 syn. nov. with the liocranid species Oedignatha scrobiculata Thorell, 1881. Castianeira albopicta Gravely, 1931 is considered as a nomen dubium. Castianeira adhartali Gajbe, 2003 and Castianeira indica Tikader, 1981 are transferred to Oedignatha Thorell, 1881 (Liocranidae). The taxonomic status of both Castianeira tinae Patel & Patel, 1973 and Castianeira quadrimaculata Reimoser, 1934 is discussed. All the examined type materials are illustrated, and the current status of the type material of each species is discussed.